Digital Literacies. - Gillen, Julia (Milton : Taylor & Francis Group, 2014)
With our increasing use of digital and online media, the way we interact with these modes has a great impact on our learning and literacy. In Digital Literacies, Julia Gillen presents a new approach to the study and research of the area.
Cover -- Half Title -- Title Page -- Copyright Page -- Dedication -- Table of Contents -- List of figures and tables -- Acknowledgements -- Chapter 1: 'No need to build caves': Digital literacies - an introduction -- Chapter 2: 'Linguistics is a discipline with its own history': Language, linguistics and digital literacies -- Chapter 3: 'Different people understand different aspects of it, but nobody knows it all': An autoethnographic approach -- Chapter 4: 'Hello': A dialogical approach to researching learning by new users of communications technologies -- Chapter 5: 'SPbT whispers: Unsquishing Rowan SParker': Approaches to the discourses of Schome Park -- Chapter 6: 'I fall in and out of love with Twitter': A case study of the development of Twitter in a professional, public media ecology - Jonathan Agnew and cricket -- Chapter 7: 'Knowledge is limited, whereas imagination embraces the whole world': Conclusions -- Bibliography -- Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books